Абревіація як новітня лексико-граматична трансформація сучасної англійської мови та труднощі її перекладу (на матеріалі медичної термінології) - Даніленко, Анастасія Юріївна; Карачова, Дар'я Володимирівна (Видавництво "Молодий вчений", 2020)
Процес абревіації у сучасному світі почав відігравати провідну роль у процесах формотворення та словотворення. Заміна звичних лексичних одиниць їх спрощеною та редукованою формою сприяє не лише раціоналізації мовленнєвої діяльності, але й оптимізації словотворчих процесів. Сьогодні помітною є тенден ція сучасної мови до економії мовних засобів, що супроводжується певним їх вдосконаленням, адже більша кількість інформація може бути передана меншою кількістю мовних ресурсів. Про це свідчить як поява вели кої кількості різного роду неологізмів-скорочень, ініціальних абревіатур, скорочених фраз, так і популярність та частотність їх використання в усіх сферах застосування мови, починаючи з повсякденного спілкування, сфери медіа та реклами, та закінчуючи діловим листуванням та науково-технічною літературою. Ключові слова: абревіація, словотворення, формотворення, редукція, переклад, мовні ресурси.

The process of abbreviation in the modern world plays a leading role in the processes of form making and word formation. Replacing the usual lexical units with their simplified and reduced forms contributes not only to the rationalization of speech activity but also to the optimization of word-forming processes. The modern world is characterized by the rapid and powerful development of information technologies and the Internet, which influence the growth of the volume of information, which immediately imprints on lexical components of different languages, which are undergoing significant changes concerning word-forming processes. This happens because of innovative technological advances that modern English has: a relatively new but productive way of word formation – shortening (abbreviation). This method of word formation is still rather poorly studied, howev er, it is becoming more relevant nowadays, as the tendency for global lexical and grammatical transformations of the language grows with each passing day and it may lead to a total change of English language in the future. The reduction, as a popular way of forming new lexical units in recent years, reflects the process of powerful lan guage transformation. Nowadays, at the epoch of technological development, saving time is extremely important. Communication takes place not only in the context of oral communication but also in increasingly popular texting messages (SMS, various messengers, social networks). Such a rapid development of a new kind of communication could not but affect different language processes. Today, such a tendency of modern language to save language resources is very noticeable and is accompanied by some improvements, because nowadays more information needs to be transmitted with fewer language resources. This can be noticed due to the nascence of a large number of different neologisms, abbreviations, abbreviated phrases, as well as the popularity and frequency of their usage in all spheres of language, starting from everyday communication and according to the media and advertising, and through business correspondence and scientific and technical literature.
Abbreviation as a New Lexical and Grammatical Transformation of the Modern English Language and Problems of its Translation (Based on Medical Terminology Abbreviations)
Keywords: абревіація; словотворення; формотворення; редукція; переклад; мовні ресурси; abbreviation; word formation; form formation; reduction; translation; language resources